An assessment of the impact of formal preparation activities on performance in the University Clinical Aptitude Test (UCAT): a national study - Sanat Kulkarni; Jayne Parry; Alice Sitch (BMC Medical Education, 2022)
Abstract Background Previous studies have shown performance in the University Clinical Aptitude Test (UCAT) to be associated with measures of candidate socio-economic advantage such as parental occupation and type of school attended. It is possible that access to preparation support and materials may in part explain these associations. In this paper we determine whether use of formal preparation resources is associated with higher UCAT scores and whether differences in use of preparation resources exist between socio-demographic groups. Methods After completing the 2017 UCAT UK school-leaver candidates (n = 14,332) were asked to answer a questionnaire regarding their use of official UCAT and commercial resources, school-based support, and time spent preparing. Multiple linear and logistic regression models were used to evaluate the associations between preparedness, demographic characteristics and UCAT performance. Results Five thousand, four hundred thirty-nine (38%) candidates responded to the questionnaire. Use of freely available UCAT official practice tests, paid commercial materials, attendance at school-based preparation courses and spending more time preparing were significantly associated with higher UCAT scores. Candidates who were from less deprived backgrounds and attending independent or grammar schools were significantly more likely to use paid commercial materials and spend longer preparing. Conclusions Reported use of preparation resources varies between candidates from different socio-demographic backgrounds and is associated independently with performance in the UCAT. Increasing the availability of freely available resources may mitigate some of these differences.